Photocatalytic asphalt mixtures: semiconductors' impact in skid resistance and texture. (31st July 2019) - Rocha Segundo, I.; Landi Jr., S.; Oliveira, S.; Freitas, E.; Costa, M.F.; Carneiro, J.
Abstract : Photocatalytic asphalt mixtures have the capability of mitigating air quality problems and degrade oils/greases by using semiconductors. The techniques to do so can change their functional characteristics. This study aimed to analyse the functionalization effect on the essential surface characteristics, such as macrotexture, skid resistance, and microtexture. AC 14 and AC 6 mixtures were functionalised with nano-TiO2 and micro-ZnO by spraying and bulk incorporation. Mean Profile Depth, British Pendulum and microtexture amplitude parameters were evaluated. TiO2 application seemed to smooth the surface slightly. In dry condition, the skid resistance of functionalised asphalt and control mixtures was similar. In wet condition, the functionalization caused a maximum decrease of 7% in skid resistance. The amplitude parameters were not affected by any functionalization technique except the skewness of AC 14 with 6% TiO2 by bulk incorporation. Furthermore, the application of the semiconductors can be used without high impacts in texture and skid resistance.